Analysis of Activity Based Costing Method as The Basis Determination of Hospital Services Rates - Christina; Bornok Situmorang (Conference Series, 2020)
The aim of this study is to get the accuracy of determining hospital rates. This study,which object is Hospital X at the city of Batam, Indonesia uses a comparative descriptive analysis method with qualitative and quantitative approaches. Cost Drivers used in this study as a cost grouping are the number of inpatient days, the number of inpatients, and floor area. The results of inpatient service calculation based on the activity based costing system at the Hospital obtained a difference for the VIP class of IDR 459,646.68 and a difference for the class I of IDR 213,252.30 where the rate set by the Hospital was higher than it should be (over value). While the difference for class II is IDR 169.50 and the difference for class III is IDR 74,088.22 where the rate set by the hospital is lower than it should be (under value).